Photoacoustic Spectrometry: A Potential Tool For Future Antioxidant Test - Suparmo Suparmo (Indonesian Food and Nutrition Progress, 2003)
Peroxidation of membrane lipid is implicated with several health disorders and antioxidants are perceived capable of controlling the reaction. Quest for new natural antioxidant dominating research topics in the last decade. Test and validation of their usefulness becoming more important, especially in vivo on human subject. Current method for peroxidation tests, such as loss of polyunsaturated fatty acids, conjugated dienes, singlet oxygen, lipid hydroperoxides and malonaldehyde provide reliable data, however, the methods are lengthy and requiring blood or urine samples. New non-invasive and quicker methods are required. Gas exhale by individual, that considered to be secondary product of lipid peroxidation are among markers candidates. Among the exhaled gases, ethylene, methane, ethane and pentane fall into the category. Ethylene and methane, however, are not specifically product of lipid oxidation. Ethylene is also produced during protein and carbohydrate oxidation, while methane is produced in a large amount by colon bacteria. Ethane and pentane are proved to be most good peroxidation marker and results are in a good correlation with the current methods. However, the two gases are produced in a very low concentration just slightlyabove that in ambient air. The detection of the twt gases utilizing gas chromatography requiring specia technique for air cleaning and concentration due to laci ofsensitivity. The laser driven photoacoustic spectrom eter is capable of detecting the two gases with more than 1000 times in sensitivity. Its uses in the detection of the two lipid peroxidation markers would be a po, tential for future peroxidation or antioxidant challenge test.